Development and impact of fuel economy standards and labels for heavy duty vehicles in Iran / Mahdi Ghazvini - Mahdi , Ghazvini (2012)
Nowadays, motor-vehicles are one the largest consumer of fossil fuels in the world. The transportation sector has the second largest contribution in oil production consumption in Iran. At this time more than 22% of oil productions are consumed by heavy motor-vehicles in transportation sector in Iran. Fuel saving initiatives such as the fuel economy standards and labels program for motor-vehicles in transportation section has been applied as purpose of decreasing the fuel consumption in many developed countries around the world. Many researched have been done on energy efficiency standards but there are few studies on economic analysis of potential efficiency improvement. In this study represents the fuel economy standards and labels programs for heavy motor-vehicles. The study found the savings has exceeded the investment cost and the program has reduced emissions caused by burning fossil fuel. The purpose of the energy labels is to provide the consumers a guideline to purchasing the most efficient motor-vehicles in market. This research has also investigated the influence of implementing the fuel economy standards and labels program on the fuel savings, economic savings and in addition the influence on the environment. Consider to the increasing of the quantity of motor vehicles in the country, many advantages will come for the society as well as the environment by using the fuel economy standards and labels program. It is predicted that by implementing this program approximately 9.3 billion liters of fuel will be saved from 2013 to 2018 also the calculated savings is about 43,802 billion in bill. The emission of carbon dioxide will decrease with the amount of around 19 million tons. Therefore, efficiency improvement of heavy motor-vehicles will give a significant impact in the future of fuel consumption in Iran. Furthermore, it has been found that implementing fuel economy standards and labels for heavy motor-vehicles causes to decrease the green house gas emissions.